Clinical characteristics and prognosis of immunosuppressed inpatients with COVID-19 in Japan. Issue 2 (February 2022) - Nomoto, Hidetoshi; Suzuki, Setsuko; Asai, Yusuke; Hayakawa, Kayoko; Gatanaga, Hiroyuki; Terada, Mari; Suzuki, Kumiko; Ohtsu, Hiroshi; Toyoda, Ako; Ohmagari, Norio
Abstract: Introduction: We aimed to analyze the clinical characteristics and outcomes of immunosuppressed inpatients with coronavirus disease 2019 (COVID-19). Methods: In this observational study, we utilized a large nationwide registry of hospitalized patients with COVID-19 in Japan. Patients' baseline characteristics and outcomes were compared according to the immunosuppressed states of the patients. The impact of different therapeutic agents on the clinical courses of the patients was evaluated. Results: Data of 14, 760 patients were included, and 887 (5.9%) were immunosuppressed. The immunosuppressed state of the patient resulted from solid tumor (43.3%, n = 384), chemotherapy within 3 months (15.6%, n = 138), collagen disease (16.9%, n = 150), use of immunosuppressive agents (16.0%, n = 142), and metastatic solid tumor (13.5%, n = 120). Immunosuppressed patients were older and had a higher severity of illness at admission and during hospitalization than non-immunosuppressed patients. The mortality rates for major diseases causing immunosuppression were as follows: solid tumor, 12.5% (48/384; P < 0.001; relative risk [RR], 3.41); metastatic solid tumor, 31.7% (38/120; P < 0.001; RR, 8.43); leukemia, 23.1% (9/39; P < 0.001; RR, 5.87); lymphoma, 33.3% (20/60; P < 0.001; RR, 8.63); and collagen disease, 15.3% (23/150; P < 0.001; RR 3.97). Underlying diseases with high mortality rates were not necessarily associated with high rates of invasive supportive care. Conclusions: The prognosis of immunosuppressed COVID-19 inpatients varied according to the different immunosuppressed states. Multiple factors, including the severity of the underlying diseases, might have affected their invasive supportive care indications.